EXPERIMENTAL STUDY ON THE USE OF ANIONIC SURFACTANT AND CO-SURFACTANT TO IMPROVE HYDRAULIC FRACTURING FLUID ADDITIVE - HUSSIEN ELHASSAN, OSMAN SALAH ELDIN (2019)
A substantial quantity of water utilized through hydraulic fracturing operation in shale reservoirs stays trapped within the formation primarily because of capillary forces.